Sedimentological characterizations of Recent sediments from the Teesta River, Bangladesh: implication for sediment transportation and depositional conditions - SOHAN, MD. SHOHANUR RAHMAN; YEASMIN, RUMANA; RAHMAN, M. JULLEH JALALUR; SAYEM, ABU SADAT MD.; RANA, MD. SOHEL (Bangladesh Geoscience Journal, 2023)
The Teesta River originates from the Higher Himalayas, flows through India and Bangladesh and transports huge sediments to the Brahmaputra-Jamuna River. Geomorphologically, the Teesta River shows braided in nature with different types of bars and floodplains. This study incorporates both the exposed sands from river banks and bars as well as subsurface borehole samples of the Teesta River with the aim of sedimentological characterization of these sediments which further assist to understand their history of transportation and deposition. The sand deposits of the Teesta River can be categorized into seven distinct lithofacies: trough cross- stratified sand (St), planar cross-stratified sand (Sp), massive sand (Sm), ripple cross-laminated sand (Sr), parallel laminated sand (Sh), massive clay (Fm) and laminated clay (Fl), which grouped into multiple fining-upward sequences, indicating periodic decrease in flow velocities as well as shifting of channels and bars. The sand deposits from channels and bars show mostly unimodal in nature which suggests unidirectional current flow, although evidence of minor redistribution by chute channels has been observed. The textural characteristics of these Teesta River sands consist of fine to medium grained, moderately well sorted to well sorted, dominantly positively skewed and leptokurtic to mesokurtic in nature. These sands are dominantly bedload deposits and have been transported predominantly by saltation process with subordinate suspension process, while traction processes are limited mainly in the upper reaches of the river. Various bivariate diagrams indicate that these sediments were deposited in low to medium level of energy conditions.